SOME DETERMINANTS OF THE PERCEPTION OF WORK–FAMILY CONFLICT: A DYADIC APPROACH - Šimunić, Ana; Pandža, Maja; Gregov, Ljiljana (Primenjena psihologija, 2017)
The general aim of this study was to examine the contribution of perceived social support from family, the quality of family functioning, attitudes about marital roles, and striving for achievement to the perceived conflict between work and family roles by using a dyadic approach. Namely, the interaction of spouses’ perceptions was taken into account (actor and partner effects) in predicting work-to-family and family-to-work conflicts. This study was conducted on a sample of 176 employed married couples in the territory of central and western Herzegovina and central Dalmatia. Self-assessment questionnaires were used. In women, social support from family was a significant predictor for both examined types of work–family conflicts, and partner effects were greater than actor effects, especially for family-to-work conflict. Both partners’ striving for achievement was a positive predictor of family-to-work conflict in women, while there was only a contribution of the actor striving for achievement to both types of work–family conflict in men. In men, the only partner effect was obtained in the relationship between social support from family and family-to-work conflict. In general, the results indicated that the assessments of male spouses were more related to their wife’s work–family conflict than vice versa, and that these variables were more related to family-to-work conflict than to work-to-family conflict.